Pengembangan Kapasitas Birokrasi dalam Rangka Peningkatan Kinerja Pelayanan Publik - Firdaus Firdaus; Ferdricka Nggeboe (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The low quality of public services in Indonesia has long been a problem that people have always complained about. This is characterized by the complex and expensive price of services, as well as the difficulty of gaining access to public services. The need and demands for quality public services become the hope of the community is urgent to be met by the government. This is in line with the current globalization trend which is characterized by the rapid advancement of science and technology so that the world becomes limitless. Nowadays, people easily get access to information both through print and electronic media, so that people are more aware and aware of their rights in obtaining services. Bureaucratic leaders at various levels, must have the same understanding and awareness to realize shared vision through accuracy and ability to make changes, and continue to develop innovation and creativity and involve all components of bureaucracy in developing bureaucratic capacity to be able to improve the performance of public services. That to provide the best service to the community, it must meet the principles of public service implementation in accordance with the basic principles that become the basis of reference in organizing, reference work, and work assessment for each public service organizing institution